The Global Credit Crunch and Foreign Banks' Lending to Emerging Markets : Why Did Latin America Fare Better? - Rai, Kulwant (IMF Working Papers; Working Paper ;, 2010)
The recent global financial turmoil raised questions about the stability of foreign banks' financing to emerging market countries. While foreign banks' lending growth to most emerging market regions contracted sharply, lending to Latin America and the Caribbean (LAC) was significantly more resilient. Analyzing detailed BIS data on global banks' lending to LAC countries-whether extended directly by their headquarters abroad or by their local affiliates in host countries-we show that the propagation of the global credit crunch was significantly more muted in countries where most of foreign banks' lending was channeled in domestic currency. We also show that foreign banks' involvement in LAC has differed in fundamental ways from that in other regions, with most of their lending to LAC conducted by their local subsidiaries, denominated in domestic currency and funded from a domestic deposit base. These characteristics help explain why LAC has not been struck as hard as other emerging markets by the global deleveraging and pullback in foreign banks' lending.